Interrupting the Pathway From Discrimination to Black Adolescents' Psychosocial Outcomes: The Contribution of Parental Racial Worries and Racial Socialization Competency. Issue 6 (16th June 2021) - Anderson, Riana E.; Jones, Shawn C.T.; Saleem, Farzana T.; Metzger, Isha; Anyiwo, Nkemka; Nisbeth, Kyle Simone; Bess, Kiana D.; Resnicow, Kenneth; Stevenson, Howard C.
Abstract : Racial discrimination can lead to psychosocial problems for Black adolescents, including internalization (e.g., depression) and externalization (e.g., conduct problems). Black parents ( N = 186; M age = 42.9) of adolescents (ages 10–18) were assessed to investigate how parental worries and racial socialization competency (i.e., confidence, skills, and stress) contribute to the association between parental discrimination experiences and their adolescents' psychosocial problems. Mediation analyses indicated that the total direct models with discrimination, worries, and problems had good fit, and that the addition of worry mediated the discrimination‐problems association. Furthermore, racial socialization competency moderated the association between worry and problems, wherein greater competency was associated with less impact of worry on problems. Findings illuminate potential intervention targets for buffering discrimination's influence on adolescents' psychosocial functioning.